2013
DOI: 10.3390/ma6125625
|View full text |Cite
|
Sign up to set email alerts
|

Facile Synthesis of Mono-Dispersed Polystyrene (PS)/Ag Composite Microspheres via Modified Chemical Reduction

Abstract: A modified method based on in situ chemical reduction was developed to prepare mono-dispersed polystyrene/silver (PS/Ag) composite microspheres. In this approach; mono-dispersed PS microspheres were synthesized through dispersion polymerization using poly-vinylpyrrolidone (PVP) as a dispersant at first. Then, poly-dopamine (PDA) was fabricated to functionally modify the surfaces of PS microspheres. With the addition of [Ag(NH3)2]+ to the PS dispersion, [Ag(NH3)2]+ complex ions were absorbed and reduced to silv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 38 publications
2
25
0
Order By: Relevance
“…FTIR spectra of samples S1, S2, S3 and S4 are acquired, and presented in Figure . The FTIR spectrum of S1 corresponds to the typical FTIR spectrum of PS reported elsewhere . Upon adding the manganese salt and NH 4 F to the PS dispersion, the FTIR spectrum (Figure ) of the resulting sample S2 shows the PS peaks which are significantly weakened.…”
Section: Resultsmentioning
confidence: 53%
“…FTIR spectra of samples S1, S2, S3 and S4 are acquired, and presented in Figure . The FTIR spectrum of S1 corresponds to the typical FTIR spectrum of PS reported elsewhere . Upon adding the manganese salt and NH 4 F to the PS dispersion, the FTIR spectrum (Figure ) of the resulting sample S2 shows the PS peaks which are significantly weakened.…”
Section: Resultsmentioning
confidence: 53%
“…It is reported that addition of metal nanoparticles can enhance the thermal conductivity and heat transfer of fluid (Sheikholeslami 2017a, b;Sheikholeslami and Vajravelu 2017). Incorporation of noble metals in polystyrene for the synthesis of composite has potential advantages in optoelectronic, catalyst, and chemical sensors applications (Alekseeva et al 2013;Zhu et al 2013;Khokhar et al 2011;Higuchi et al 2016). Xia et al (2014) increased the power conversion efficiency of organic/Si hybrid solar cells by incorporating of gold into poly (3,4-ethylenedioxythiophene)/polystyrenesulfonate due to light trapping.…”
Section: Introductionmentioning
confidence: 99%
“…The molar ratio of monomer NIPAM, crosslinker N,N ′‐methylenebisacrylamide, and initiator potassium persulfate was 200:10:3. The resultant PNIPAM nanogels were purified by centrifugation at 8000 rpm and 10 ºC, and then freeze‐dried for 48 h. Subsequently, 0.5 g dried PNIPAM nanogels were well dispersed into 100 mL of tris hydrochloride buffer (15 × 10 −3 m , pH = 8.5), and then 0.2 g dopamine was added to form the PDA layer on the PNIPAM nanogels at 25 ºC for 2 h . The resultant PDA coated nanogels were washed by centrifugation.…”
Section: Methodsmentioning
confidence: 99%